Natural small molecule smart hydrogels inhibited the Hsp90/NF‐κB signaling axis in inflammation to achieve sustained antipyretic effect - Yuqin Yang; Jingyi Jiao; Xiaohui Jia; Lei Li; Meiling Wu; Xinyue Lu; Yangyang Sun; Yingqi Lang; Fuhao Chu; Dong Bai; Penglong Wang; Haimin Lei (Journal of Nanobiotechnology)
Abstract In general, pseudoephedrine (PE) is a safe and universally employed in cold medicine, which displays powerful effect on antipyretic. Nonetheless, the sustained drug delivery system can effectively put an end to the above problems attributable to the drawbacks of low bioavailability and short intervals of administration. “Complexation” hydrogels are capturing enormous attention in a diverse array of fields in that there is no necessity to carry out external intervention for drug delivery. Nevertheless, it is prevalently acknowledged that macromolecular “complexation” hydrogels, biotin/avidin, antibodies/antigens, heterodimers, conA/glucose and cyclodextrin (CD) inclusion complexes, have several limitations of conventional drug delivery systems, such as unfavorable biological safety, undesirable intestinal wall penetrating, and extremely limited biodegradability, etc. For this reason, it is tremendously imperative to develop a natural small “complexation” hydrogel. In this context, we innovated a direct self-assembly “complexation” hydrogel (PE-GA). The PE-GA hydrogel was prepared by the incorporation of PE and glycyrrhizic acid (GA) into an aqueous dispersion without the aid of other carriers, which demonstrated dual-responsiveness including heating–cooling as well as pH. It is mainly governed by hydrogen bonds and electrostatic interactions. For cell bioavailability, there were substantial discrepancies between the PE-GA hydrogel and free PE at 72 and 84 h. For pharmacokinetic properties, there was also conspicuous discrepancy in Area Under the Curve (AUC) values between them. In subsequent antipyretic assay, PE-GA hydrogel displayed a conspicuous antipyretic effect in fever rats induced by LPS. The non-invasive fluorescence imaging was utilized to monitor the intestinal retention of the PE-GA hydrogel in mice, its unique aggregation/assembly induced retention (AIR) effect reinforced bioactive molecule retention, which may be another manifestation of enhancing antipyretic effect. Aside from that, PE-GA hydrogel played an antipyretic role by Hsp90/NF‐κB pathway. The current research revealed potential antipyretic effect of PE-GA hydrogel which could be the therapeutic option against fever. Graphical Abstract